Systematic operational budgeting: the preliminary study on perception of SMEs entrepreneurs / Norhayati Zamri, Norul Akma Mansor and Liyana Ab Rahman. - Zamri, Norhayati; Mansor, Norul Akma; Ab Rahman, Liyana (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2018)
Inability to acquire and comprehend the required financial and management skills are blamed to be the fathom of failures of small medium enterprises (SMEs) in Malaysia, as reported by Beh (2013). Small business is a critical contributor to Malaysia's economic recovery and strength, to building Malaysia's future and to compete in today's ever-challenging global marketplace. Realizing the above, it drives the current study to investigate i) the perception of the SMEs entrepreneurs in budgeting and record keeping and ii) the need for a systematic operational budgeting to assist SMEs entrepreneurs in recording basic costing transactions. The findings of this study have implications for SMEs entrepreneurs in Malaysia. It will contribute to existing literature which highlight the lack of systematic operational budgeting among SMEs entrepreneurs in rural areas. Therefore, there is a need for the proper budgeting system that lead for better SMEs transformation and empower entrepreneurship towards a sustainable economy.